Jeannette Thurber Connor collection of Floridiana - Connor, Jeannette Thurber, -1927.; Archivo General de Indias
Correspondence; speeches; writings; reports; research material; transcripts of documents in English, French, and Spanish repositories, primarily the Archivo General de Indias, Seville, Spain; maps; surveys; photographs; and other papers relating to the early history of Florida, chiefly during the period as a Spanish colony.
Historian. Born, 1872.
Collection material in English, French, and Spanish.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Card indexes for certain files available in the Library of Congress Manuscript Reading Room.
Keywords: Florida -- History; Florida -- History -- To 1821.; Spain -- Colonies -- America; Historians